The Role of a Digital History Book in Implanting Heroic Values for the Millennial Generation - Fathoni, Baharuddin; Sutimin, Leo Agung; Purwanta, Hieronymus (Universitas Malikussaleh, 2021)
Facing the era of globalization, the younger generation continues to experience an identity crisis where the younger generation is more familiar with hero figures who do not reflect eastern values, especially those that are typically Indonesian which causes the young generation to lack concern for the nation; and reduced pride in Indonesia's nationalistic identity. Digital books or e-books are a technological development that utilizes computers used to display information in the form of text, images, audio, video and other multimedia in a concise and dynamic form that can be read by computers or other electronic devices. In this case, digital books are an alternative and the right solution for learning the history of heroism in the implementation of independent learning. The purpose of this paper is to determine the role of digital history books in teaching heroic values to students. This research is analyzed using qualitative research methods. The results and discussion are: the role of learning the history of heroes through digital book media that can make it easier to teach heroic values to students. So that students are able to emulate heroic values and actualize and serve as spirit values in the life of society, nation and state.